DRUG PREVENTION TRAINING FOR YOUTH: BUILDING CHARACTER AND RESILIENCE OF THE MUSLIM GENERATION IN THE MODERN ERA - Muhammadong, Muhammadong; Muthmainnah, Sitti; Khaerunnisa, Khaerunnisa; Nurhilaliyah, Nurhilaliyah (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to strengthen the moral character and resilience of Muslim youth in facing modern challenges, especially the increasing threat of drug abuse. The method used is a participatory and educative approach through interactive seminars, focus group discussions, and role-play activities that emphasize preventive awareness based on Islamic moral values. The training materials include knowledge about the dangers of drugs, Islamic teachings on self-control and health, as well as strategies to develop resistance against negative social influences. The participants, consisting of students and young community members, are guided by a team of educators, health professionals, and religious leaders to ensure holistic learning outcomes. The implementation process is supported by pre- and post-assessments, observation, and participant reflection to evaluate the level of understanding and behavioral improvement. The results show that this activity effectively increases awareness, strengthens personal values, and builds resilience among youth. In conclusion, the integration of religious and educational approaches in drug prevention training plays an essential role in forming a generation of Muslims who are morally upright, aware of social risks, and capable of making positive life choices in the modern era.